Towards Jamie McCallum (Dir.), The Real Work - Anastasova, Senka (Identities: Journal for Politics, Gender and Culture, 2018)
Author(s): Senka Anastasova Title (English): Towards Jamie McCallum (Dir.), The Real Work Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 204-209 Page Count: 6 Citation (English): Senka Anastasova, “Towards Jamie McCallum (Dir.), The Real Work,” Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 204-209.